Manajemen Komunikasi dan Kinerja Pustakawan - Yuriyan Dinata; Rini Setyaningsih (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The purpose of this study was to find out how the communication and performance of librarians at the library of UIN Sultan Syarif Kasim Riau. The research method that the author uses is a qualitative method using a case study approach. The research subjects were Associate Expert Librarians, and one other librarian staff, as well as 5 library visitors. The object of research is the communication and performance of librarians. The data obtained through data collection techniques using observation, interviews, and documentation. The results of this research, the authors found that communication and performance are interrelated and influence. Good communication triggers good librarian performance as well, and increases the satisfaction of library visitors. Communication and performance are interrelated with each other. Good and proper communication will bring an organization to be even better, without exception, libraries which involve a lot of communication on the subject. A librarian is required to be friendly and polite in serving visitors, which means that they must communicate properly and correctly. Good communication will increase the satisfaction of library visitors and affect the librarian's performance, either increasing or decreasing.